The Effect of Using Cooking Academy Game towards Students’ Writing Ability - Nofrika Sari; Hayatin Nufus (AT-TA'LIM, 2016)
This study is an experimental research that discussed the impact of the use of cooking academy game in teaching writing on the students’ ability in writing procedure text at class VII Junior Secondary School I Pangkalan Baru Lima Puluh Kota. This study was aimed to determine the effects of the use of cooking academy game towards the student's ability in writing procedure text. In this study, the population is the students of class VII, while sample are two classes: one class for the experimental class and another class for control. Samples were drawn randomly. Data were collected by giving pre-test and post-test on the sample. Data were, then, analyzed applying t-test formula. The results showed that students who were taught to write text using the procedure of cooking academy game has the ability to write higher than students who are not taught by using games cooking academy.